2009
DOI: 10.1177/205157070902400203
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Product Package on Functional and Symbolic Associations of Brand Image

Abstract: This article examines the influence of the product package (color and shape) on some functional (brand belief) and symbolic associations (brand personality) of the brand image. Hypotheses are tested in an experiment that results in an empirical validation of the role of the package in the brand image enhancement process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 53 publications
1
31
1
1
Order By: Relevance
“…In addition, the association between colour choice and the shape of the product can be manipulated to convey or modify a specific brand image. For example, choosing round shapes and warm colours contributes to conveying messages of sophistication and femininity . This is supported by Brakus et al who addressed the importance of using unique colours and shapes.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, the association between colour choice and the shape of the product can be manipulated to convey or modify a specific brand image. For example, choosing round shapes and warm colours contributes to conveying messages of sophistication and femininity . This is supported by Brakus et al who addressed the importance of using unique colours and shapes.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, a change in the package design may change the consumer expectations regarding product taste or level of quality (Ares et al., ; Becker, van Rompay, Schifferstein, and Galetzka, ; Mizutani et al., ; Rebollar, Lidóna, Serranoa, Martín, and Fernández, ; Sester, Dacremont, Deroye, and Valentin, ; Smets and Overbeeke, ; Westerman et al., ). Such changes are also likely to modify the perception of the brand personality or image (Orth and Malkewitz, ; Pantin Sohier, ). This research showed that specific visual codes are associated with a specific product category and therefore define the package perceived typicality in that category.…”
Section: Discussionmentioning
confidence: 99%
“…The red bottle is perceived as more sportive than the blue bottle. In addition, elongated bottles are seen as more sophisticated than short and large bottles . Labrecque and Milne showed that packaging or logo colours such as black, purple and pink influence the perceived sophistication of a brand.…”
Section: Packaging and Inference‐makingmentioning
confidence: 99%